3D X-ray imaging of Precambrian microfossils: evaluating biogenicity at the nanoscale with ptychographic X-ray computed tomography - Peres, Lara Maldanis Cerqueira (2019)
Precambrian microfossils are structures difficult to be investigated by means of conventional imaging approaches due to their small size, geochemical composition and relative scarcity that limits the use of destructive methods. One recurrent problem in the study of these earliest life forms relies on attesting their biogenicity given that structures formed abiotically can strongly resemble fossilized cells of simple morphology. The search of novel analytical methods for contributing to the evaluation of these ancient structures if of great importance for the development of the field of Precambrian paleobiology. In this work, the coherent X-ray imaging approach of ptychographic X-ray computed tomography is explored for assessing bona fide microfossils from the Gunflint and Draken Formations, and early Archean controversial structures described as fossil bacteria from the Hoogenoeg and Kromberg Formations of the Barberton Greenstone Belt. The microfossils were imaged non-destructively in 3D with nanometric resolution and quantitative electron density contrast, which allowed the estimation of mass density of the materials. The tomographic images provided information on both the morphology and geochemical composition of the specimens at the nanoscale within a microscale context. From the morphological data, it was possible to distinguish the 3D distribution of kerogenous material, which revealed a novel preservation pattern and traces of taphonomical alterations for filaments of Gunflint Formation, and ultrastructural details preserved in cell walls of specimen from Draken Formation. The mass density quantification provided supporting evidences, such as the discrimination of kerogen maturation states and identification of minerals, providing also a picture of the taphonomical history of the specimens. Based in the biogenicity criteria investigated at the nanoscale, we could not attest the biogenicity of the structures described in the Barberton Greenstone Belt, but we offered new possible interpretations of biological and biotic origins for the formation of these structures. The results represent significative advances for the comprehension of fossilized microorganisms and add important contribution for the assessment of biogenicity through a robust combination of morphological and geochemical 3D information from the nano to the micron-scale.